VARIASI BAHASA ARAB PADA PENUTUR BAHASA MALTA DALAM TATARAN FONOLOGI - Alya Zahra; Rika Astari (`A Jamiy : Jurnal Bahasa dan Sastra Arab, 2021)
This article aims to analyze the types of Arabic phonological changes in Maltese speakers. This research is included in the qualitative research using the intralingual equivalent method. The results showed that there were many phonological variations of Fusha Arabic in Maltese, including: (1) Lenisi consisting of apocope, syncope, changing vowel /i/ to vowel /a/, changing vowel /i/ to sound vowel /ɛ/, change in vowel sound /u/ into vowel sound /ɛ/, change in vowel /u/ into vowel /o/, and change in vowel /u/ into vowel /a/, (2) Sound substitution consonants with consonant sounds consisting of changes in consonant sound // into consonant sound /t/, consonant /q/ into consonant /ʔ/, consonant /x/ into consonant /ħ/, consonant /ðˤ/ into consonant /d/, consonant /dˤ/ becomes consonant /d/, consonant /tˁ/ becomes /t/, consonant /sˁ/ becomes consonant /s/, and consonant /t/ becomes consonant /d/, (3) Epenthesis, 4) Diphthongization, ( 5) Monophthongization, and (6) Sound reinforcement consisting of changing the vowel sound /a/ into a vowel sound /ɛ/, changing the vowel sound /a/ into a vowel sound /i/, and Consonant sound /t/ changes to a consonant sound /d/.